Data science for marketing analytics : a practical guide to forming a killer marketing strategy through data analysis with Python /: a practical guide to forming a killer marketing strategy through data analysis with Python. (2021) - Baig, Mirza Rahim; Govindan, Gururajan; Shrimali, Vishwesh Ravi
No abstract available